Spirulina (Arthrospira platensis) as an alternative ingredient for 3D printed white chocolate - Erunsal, Sevil Cikrikci; Karabiyik, Munevver Beyza; Inac, Hanife Nur; Kirdi, Kardelen Sena (SPRINGER, 2026)
3D food printing offers a unique opportunity to enhance the appeal of less conventional ingredients, such as microalgal biomass, by enabling innovative designs and personalized nutrition. However, the success of printed formulations depends on ingredient composition and predefined design settings. This study investigated the incorporation of Spirulina, a nutrient-rich microalgae, into white chocolate to enhance its nutritional value, antioxidant potential, and printability as well as to achieve on-demand customization. White chocolate alone was unprintable due to insufficient viscosity, while the best printability was observed with 5.36% (w/w) Spirulina. Moisture content remained largely unchanged with Spirulina addition, but the whey powder-containing sample (CSW) exhibited increased moisture levels, softening the chocolate texture. Rheological analysis showed that whey protein (WP) significantly increased viscosity, with the CSW sample reaching similar to 10.5 Pa.s at 100 s(-1) shear rate, which may be excessive for ideal printing. The CS sample (Spirulina only) had an optimal viscosity range (5-10 Pa.s), allowing successful extrusion. Furthermore, Spirulina addition enhanced the antioxidant activity by similar to 10-11% compared to the control. The optimized CSW ink demonstrated a balance of printability, texture, and enhanced nutritional properties, making it a promising alternative for functional chocolate applications. These findings highlight the potential of 3D food printing to develop customized, nutrient-rich chocolate products, meeting consumer demand for personalized and sustainable food innovations.
Keywords: Chocolate printing; Functional food; Microalgae incorporation; Nutrient-enriched chocolate; Spirulina; Food Science & Technology